Hepatocellular Carcinoma Metastasis to Sphenoid Wing. (April 2013) - Pirbhai, Adnan; Kahawita, Shyalle; Davis, Garry; Dodd, Tom; Thomas, Josephine; Selva, Dinesh
ABSTRACT We present a case report where hepatocellular carcinoma metastasis to the sphenoid wing was the initial presentation of an occult primary.